ACUTE INTESTINAL OBSTRUCTION IN ELDERLY AND SENILE PATIENTS - Khudoyberdiev, S.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
One of the first ancient scholars to describe in detail all aspects of acute intestinal obstruction is Abu Ali Ibn Sino (980-1030), known in Europe as Avicenna. His description of acute intestinal obstruction in the multi-volume treatise "Canon of Medicine" (Book 3, Part 16, Treatise 3) presented the name of this pathology as "qoolinj" and "ehtebase sofl" (stool retention). "Qoolinj" and "ilavos" are intestinal diseases characterized by a pain syndrome that leads to difficulty in defecation. The causes of "qoolinj" are in and around the large intestine, while the origin of "ilavos" is in the small intestine. Based on the symptoms and their causes, "qoolinj" and "ilavos" are included in different types, and the obstructive type can be considered the equivalent of bowel obstruction in modern medicine. Avicenna said that the cause of "qoolinj" and "ilavos" may be an obstruction that blocks the passage of feces and gas. Thus, it leads to severe distension of the intestines and abdominal pain. Truly described in reality corresponds to many aspects of the etiology, pathogenesis and clinical manifestation of acute intestinal obstruction, the current problems of which we describe in this review article.